Lithology-Based 3D Modeling of Urban Geological Attributes and Their Engineering Application: A Case Study of Guang’an City, SW China - Zhou, Fang; Li, Minghui; Huang, Congjun; Liang, Hong; Liu, Yujie; Zhang, Jianlong; Wang, Baodi; Hao, Ming (Frontiers in Earth Science, 2022)
Urban geological modeling (UGM) is a fundamental approach for the visualization of underground space and recognition of complex geological conditions of a city. Previous UGM studies, with the assumption of homogeneous geological characteristics, have resulted in deviated modeling properties due to negligence of parameters with obviously different spatial distribution in lithologies. This study presents a case study of Guang'an city in SW China by using a sequential simulation interpolation(SSI) method that reflects geological heterogeneity by combining field surveys, topography, borehole data, geological profiles, and stratigraphic columns to establish a lithology distribution model in the study area. The geotechnical attribute model of the area of interest was established based on lithology to capture subtle variations in lithology due to obvious differences in geotechnical characteristics of clay, sand, mudstone, sandy mudstone and argillaceous sandstone. This 3D model could provide a reference for the urban underground space master planning and future sustainable development of Guang'an city. Besides, this study also discusses the prospects and directions of urban geological modeling and provides a few suggestions for engineering in urban area.